Focus on grammar : 1 / Irene Schoenberg, Jay Maurer - Schoenberg, Irene
Through controlled and communicative exercises this text helps students to bridge the gap between identifying grammatical structures and using them. Each unit progresses through four steps: grammar in context, grammar presentation, focused practice and communication practice. Includes circling, matching, filling-in-the-blank, underlining, correcting, completion, short answer and writing exercises.